Pentingnya Aktivitas Pemanasan ( Warming Up ) dalam Mendukung Keberhasilan Kegiatan Olahraga di Sekolah Dasar - Saskhia Rahmadani; Shofiatul Izza Marpaung; Rachel Dewi Putri Silalahi; Najwa Arisha Putri; Fajar Sidik Siregar (Student Research Journal, 2024)
Warming up is a routine that should be carried out before doing more intense activities. Warming up serves to prepare the body to be better able to perform activities with less risk of injury. This research was conducted to analyze the importance of warm-up activities in supporting the success of sports activities in elementary schools. This research is processed by the literature review method to analyze the importance of warming up activities in supporting children's success in sports in elementary schools. The results of the analysis show that this research has various aspects, namely: the benefits of warming up in sports activities in elementary schools, effective warm-up methods for children, and the suitability of warm-up methods for elementary school children.